Advances in the development of hemostatic biomaterials for medical application - Yong Kiel Sung; Dae Ryeong Lee; Dong June Chung (Biomaterials Research, 2021)
Abstract Background Medical hemostatic biological materials are necessary for the development of the process of preventing and stopping damaged intravascular bleeding. In the process, some red blood cells and white blood cells are trapped in nets. The resulting plug is called a blood clot. This is often a good step in wound healing, but separation of blood clots from blood vessel walls can cause serious health problems. Main body The advance in the development of hemostatic biomaterials is necessary for biomedical application. Firstly, the historical background of artificial hemostasis has been included and the current research of hemostasis has been included in more detail. Secondly, the current research of hemostasis has been included on the oxidized cellulose-based hemostatic biomaterials such as starch based on composite cross-linking hemostatic networks, hemostatic materials on NHS-esters, hemostatic agent from local materials and biomaterials for hemostatic management. Thirdly, polysaccharide hemostatic materials, bio-inspired adhesive catechol-conjugated chitosan, mesoporous silica and bioactive glasses for improved hemostasis, minimally invasive hemostatic biomaterials and chitosan-base materials for hemostatic application have been included. Fourthly, the biological properties of natural hemostatic agent by plasma technology and the hemostatic agents based on gelatin-microbial transglutaminase mixes have been also included. Conclusion Current research on hemostasis includes hemostatic biomaterials such as cellulose-based hemostatic starch based on a complex cross-linked hemostatic network. It also includes polysaccharide hemostatic materials, biomimetic adhesive catechol-binding chitosan, mesoporous silica or physiologically active glass for hemostatic improvement, minimally invasive hemostatic chitosan-based materials, and gelatin-microbial transglutaminase-based hemostatic agents. Future studies should focus on modular combination of hemostatic imitation and reinforcement mechanisms of different materials and technologies to find the optimal system to promote and strengthen active platelet or platelet imitation aggregation in bleeding sites. The second optionally increases the production of thrombin and fiber formation at the site. Third, the formed fibrin biopolymer network has strengthened to reduce thrombosis and amplify hemostasis.